The Digital Transformation Competences for Brazilian Automotive Managers: A Transdisciplinary Engineering Approach - Ribeiro, Vagner Batista [UNESP]; Muniz, Jorge [UNESP]; Mosconi, Elaine; Nakano, Davi (IOS Press, 2024)
New technologies related to Digital Transformation (DT) and the Industry 4.0 (I4.0) modify the way business and productive processes are carried out, generating complex changes for industry and engineering, establishing new tasks and human roles, and interacting with the characteristics of Transdisciplinary. Digital engineering managers play an integrative role by relating and using the organisation's digital technological knowledge to generate better business results. The characterization of managers' competences to guide and stimulate value creation in industrial sectors is still not sufficiently investigated and emerges as a critical element for industrial development in the digital age. This research fulfils this gap and aims to rank four types of necessary competences for engineering managers facing the DT/I4.0 in the automotive sector. The methodological approach adopted is quantitative, based on the judgement of engineering managers from the Brazilian automotive sector, which is globally representative in terms of productivity. An Analytic Hierarchy Process (AHP) is applied in the data treatment. Results are based on a sample of 35 interviews from six automotive companies with different levels of complexity in production operations and formal programs for DT/I4.0 implementation. Findings indicate the relative priority for the digital technical, managerial, social, and motivational competences, presenting insights with implications to guide the development of the digital engineering managers.
Keywords: Automotive Sector; Competence; Digital transformation; Engineering managers; Transdisciplinary engineering